Revenge of the living dummy [compact disc, unabridged] - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2008)
The thrill ride begins when 12-year-old Britney Crosby encounters an old ventriloquist's dummy with a lively secret - and a wicked plan. Just when she thinks the nightmare is over, Britney receives an invitation to an amusement park where everything is not as it seems. Who - or what - is summoning ordinary kids to HorrorLand? Britney and her friends must find out fast, or remain trapped forever in the scariest place on Earth.